The Effect of the Implementation of POJK 34/2024, Top Management Support, and Organizational Culture on Company Performance Through Human Resource Quality at PT. Dekai Reinsurance Broker - Angga Arifiyanto; I Made Indra P (Jurnal Impresi Indonesia, 2026)
This study analyzed the influence of the implementation of Financial Services Authority Regulation (POJK) Number 34 of 2024, top management support, and organizational culture on company performance through human resource quality as a mediating variable at PT Dekai Reinsurance Broker. The research background was based on regulatory changes in the Indonesian insurance and reinsurance industry that required adjustments in governance, professionalism, and employee competency development. The study employed a quantitative approach using a survey method and Structural Equation Modeling based on Partial Least Squares (PLS-SEM) analysis with SmartPLS 4 software. The research sample consisted of 43 internal respondents selected using a saturated sampling technique. The results showed that the implementation of POJK 34/2024 provided the largest substantive contribution to improving human resource quality, while human resource quality had a positive and significant effect on company performance, with a path coefficient of 0.508 (BCa 95% CI: 0.011–0.876). Top management support showed only a marginal positive effect on company performance, while organizational culture was not proven to have a significant effect on human resource quality or company performance. Furthermore, human resource quality was not proven to mediate the relationship between the three independent variables and company performance. These findings highlight the importance of effective regulatory implementation, continuous improvement of human resource quality, and sustained management commitment in supporting company performance. This research contributes theoretically to the development of human resource management and policy implementation studies, while also providing practical implications for reinsurance brokerage companies in designing integrated competency development and governance strategies.